Designing a Web-Based Influencer Marketing System to Increase Brand Influence and Authority - Laksana, Shifa Al-Fathia; Putra, Fadhil Irmani; Ginasta, Nava Gia (Journal of Digital Business and Innovation Management, 2024)
Social media and online platforms are key in building and strengthening brands in the digital era. Influencer marketing is a strategy that involves influential individuals on social media, becoming popular to increase brandreputation. However, brands often have difficulty identifying the right influencers, managing relationships with influencers, and measuring campaign effectiveness. This research aims to design a web-based influencer marketing system to help brands overcome this challenge. This system will increase brand influence and authority in the digital world, strengthen customer relationships, and increase influencer marketing transparency. The research managerial implication is that companies can understand user needs and preferences more deeply from an influencer and brand perspective. This allows them to design more intuitive interfaces, easy navigation, and features that facilitate collaboration and content management, as well as identify crucial features to introduce in an influencer marketing website system.